2018
DOI: 10.1007/s10803-018-3803-7
|View full text |Cite
|
Sign up to set email alerts
|

Mock Juror Perceptions of Credibility and Culpability in an Autistic Defendant

Abstract: One-hundred-and-sixty jury-eligible participants read a vignette describing a male who was brought to the attention of police for suspicious and aggressive behaviours and displayed atypical behaviours in court. Half of participants were informed that he had autism spectrum disorder (ASD) and were given background information about ASD; the other half received no diagnostic label or information. The provision of a label and information led to higher ratings of the defendant’s honesty and likeability, reduced bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 94 publications
5
36
0
Order By: Relevance
“…We also hypothesized that the relationship between ASD diagnosis and perceived deception and credibility would be moderated by the knowledge that the target individual is on the autism spectrum. This hypothesis is not only consistent with Kelley's (1971) discounting principle but also with emerging evidence that providing information on an individual's ASD diagnosis results in more positive interpersonal judgments (Maras, Crane, et al, 2019;Maras, Marshall, et al, 2019;Matthews et al, 2015;Sasson & Morrison, 2019). For example, Maras, Marshall, et al (2019) found that mock jurors who were informed that a defendant was autistic perceived the defendant as more honest and less guilty than those who were not informed of his diagnosis.…”
Section: The Studysupporting
confidence: 78%
See 1 more Smart Citation
“…We also hypothesized that the relationship between ASD diagnosis and perceived deception and credibility would be moderated by the knowledge that the target individual is on the autism spectrum. This hypothesis is not only consistent with Kelley's (1971) discounting principle but also with emerging evidence that providing information on an individual's ASD diagnosis results in more positive interpersonal judgments (Maras, Crane, et al, 2019;Maras, Marshall, et al, 2019;Matthews et al, 2015;Sasson & Morrison, 2019). For example, Maras, Marshall, et al (2019) found that mock jurors who were informed that a defendant was autistic perceived the defendant as more honest and less guilty than those who were not informed of his diagnosis.…”
Section: The Studysupporting
confidence: 78%
“…Consistent with the findings of Maras, Crane, et al (2019), the results of our study indicated that autistic individuals were rated as less deceptive and of higher character when observers were provided with information about their ASD diagnosis. This suggests that appropriate disclosure of an ASD diagnosis, in conjunction with relevant education on autistic behaviors, may be an effective way to reduce the negative bias toward people on the autism spectrum (Maras, Crane, et al, 2019;Maras, Marshall, et al, 2019;Sasson & Morrison, 2019). However, Maras, Crane, et al (2019) caution that research in this area is still preliminary and a better understanding of the mechanisms through which credibility judgments are formed would be necessary to determine how these principles can be applied effectively by stakeholders.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…White et al, 2020), who fear that autism-related stigma can harm how they are viewed by others (Jones et al, 2015) and increase their risk for experiencing discrimination and victimization (Zeedyk et al, 2014). Indeed, although NA perceptions of autistic people do improve on average when informed of their diagnosis (Maras et al, 2019;, disclosure is not always a beneficial strategy. In some contexts, disclosure can have little to no effect (R. White et al, 2020) or even be detrimental depending on the autism-related stigma held by the person receiving the disclosure (Morrison et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research shows that disclosing one’s autism diagnosis can have a profound effect in improving others’ perceptions of them both in everyday contexts (e.g. Brosnan & Mills, 2016 ; Morrison et al, 2019 ; Sasson & Morrison, 2019 ) and in specific settings such as the Criminal Justice System ( Crane et al, 2018 ; Maras, Crane, Walker, & Memon, 2019 ; Maras, Marshall, & Sands, 2019 ). Future research should examine whether diagnostic disclosure has a similar impact upon employer perceptions and whether disclosure together with adaptations to questions is enough to diminish differences in employers’ overall impressions between autistic and non-autistic interviewees.…”
Section: Discussionmentioning
confidence: 99%